Potensi Chitosan Sebagai Bahan Irigasi Dalam Pembersihan Smear Layer Saluran Akar - Rina Permatasari; Erisa Ekiyo (Faculty of Dentistry Universitas Andalas, 2023)
Background: Smear layer is formed after root canal preparation. Removing the smear layer is an important aspect because it can affect the adaptation of sealer so it can increase the leakage of the root canal filling. Chitosan is a natural biopolymer produced by the deacetylation of chitin which has a chelation effect. Purpose: To explain the potential of chitosan as an irrigant on smear layer removal in root canal. Method: Based on sources obtained from journals, textbooks, and websites accessed through the Google Scholar database. The types of references taken are in the form of research reports, literature studies, published from 2014–2021. Conclusion: Chitosan has the potential as root canal irrigant for smear layer removal even in low concentrations with minimal side effects. However, there are differences of opinion regarding the region of smear layer removal.